The Article is Not Enough: Introducing the JLSC Data Sharing Policy - Journal of Librarianship and Scholarly Communication (Journal of Librarianship and Scholarly Communication, 2014)
As data publication and data citation emerge as best practices in scholarly communication, the JLSC editorial board has considered its own position regarding a data publishing policy, and has explored the elements of such a policy most appropriate for our community at this time. Our view is that the scholarly record is strongest when the data underlying any report of research findings are accessible at the time of publication and into the future to enable other investigators to reproduce the research and to build on it through additional studies. Additionally, we recognize that data publication and citation are important practices to ensure data providers receive credit for their valuable research contributions. Finally, we understand the importance of making all publiclyfunded research data openly available so that society may fully benefit from its investments in the creation of these knowledge assets. For this combination of reasons, JLSC shall introduce a data policy effective August 1, 2014 that will be subject to revision in order to reflect ongoing developments in practices and infrastructure in this area.